Can glassforming liquids be 'simple'?. (June 2019) - Brazhkin, V V
Abstract: The tendency of various types of liquids to vitrify at moderate cooling rates is discussed. Good glass-forming liquids–covalent melts, polymer and organic liquids–feature high viscosity values of 10 −2 – 10 7 Pa s at temperatures close to the melting point. The glasses obtained by cooling such liquids are nonergodic systems, i.e., their properties are not unambiguously defined by external parameters. At the same time, many glass-forming molecular liquids are usually considered to be 'simple' systems described by an effective pair central potential of interaction between particles. In particular, the scaling of thermodynamic and transport characteristics for varying temperature and density and behavior under pressure of the melting temperature and the bulk modulus of molecular liquids are well described by the parameters of a simple effective pair potential. It is shown that the values of the viscosity of glassy molecular liquids in no way correspond to the effective-potential parameters (in contrast to the viscosity of true 'simple' fluids, such as liquefied inert gases). Due to the complex structure of the molecules of such liquids, the effective-potential parameters heavily depend on the distance between particles. A complex set of intermolecular and interatomic chemical bonding emerges when such liquids are vitrified. Thus, glass-forming molecular liquids can only be considered 'simple' from the point of view of their thermodynamic properties, while the polyatomic structure of their molecules results in a 'complex' behavior of transport characteristics and anomalously high viscosity values.